DEFINITION OF TYPOS IN ANSWER OF STUDENT IN KNOWN CORRECT ANSWER - Maria V. Biryukova; Dmitry P. Mamontov; Oleg A. Sychev (Открытое образование (Москва))
The paper describes method of typo detection in the answers for the questions with open answers. In such questions we know one or several correct answers defining relatively small dictionary of correct words contrasting the usual case of looking for typos in arbitrary text. This fact allows using more complex analysis methods and finding more possible typos, such as extra or missing separators. A typo correction module for the Correct Writing question type (for Moodle LMS) was developed using proposed methods.